PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KUPUTUSAN PEMBELIAN DI HARUM BAKERY CURUP - Wahyudi, Julizar Dwi; Ilhami, Mardhiyah Dwi (UM. Bengkulu, 2025)
This research was conducted at the Harum Bakery Curup Shop. The aim of this research was to find out whether Service Quality and Location influence Purchasing Decisions at Harum Bakery Curup. The sample in this study was 160 respondents, data analysis techniques used interviews and questionnaires. Based on the results of research conducted on the influence of service quality and location on purchasing decisions at Harum Bakery Curup, it can be concluded as follows: Quality has a significant influence on purchasing decisions at Harum Bakery Curup. Location has a significant influence on purchasing decisions at Harum Bakery Curup. Service quality (X_1) and location (X_2) together have a significant influence on purchasing decisions (Y) at Hatum Bakery Curup.Keywords: Service Quality, Location, Purchasing Decisions